Notes on the glosses of Foscolo's "Discourse on the text of Dante's Comedy" and commentary on a 'quaker' note (Prassi Ecdotiche della Modernità Letteraria, 2018)
The Livorno copy of the first edition of Foscolo's Discorso sul testo della Commedia di Dante is a paradigmatic case of a volume glossed by the author himself. The present work aims at providing a first analysis of the said glosses and of the editorial solutions adopted in the Edizione Nazionale. In particular, the study focuses on the comment of an autograph gloss that may bring new insight into Foscolo's idea of Dante as religious reformer and into the relationship between the late Foscolo and the Quaker community during the poet's final years in London.
Keywords: Foscolo; Robert Barclay; William Allen; annotations; notes; quakers; Dante